THE POTENTIAL OF CNT-PVA MEMBRANE AS A GREEN TECHNOLOGY ALTERNATIVE - Hutapea, Henny Parida; Ambarwati, Septiana; Putri, Rafika Aulia; Aulia, Michell (LPPM Universitas Duta Bangsa Surakarta, 2025)
The development of advanced membrane technologies is essential for addressing environmental challenges, particularly in wastewater treatment and oil-water separation. Polyvinyl alcohol (PVA) is a hydrophilic, environmentally friendly polymer commonly used for membrane fabrication; however, it suffers from high swelling and low mechanical strength, which limits its long-term performance. To overcome these drawbacks, carbon nanotubes (CNTs) were incorporated into the PVA matrix to form PVA-CNT composite membranes. CNTs serve as structural reinforcements, enhancing mechanical strength, thermal stability, and inter-chain bonding within the PVA network. The interconnected pore structure and high conductivity of CNTs also improve membrane selectivity and reduce swelling by stabilizing the polymer structure when exposed to water or aqueous solutions. Additionally, the modified surface properties provided by CNTs result in superior fouling resistance, minimizing pore blockage and maintaining water flux over extended operation periods. This study demonstrates that PVA-CNT composite membranes offer a sustainable and energy-efficient solution for separation processes, making them highly suitable for oil-water separation, industrial wastewater treatment, and other filtration applications such as water purification and organic compound removal. The findings highlight the potential of PVA-CNT membranes as a green technology that combines high performance with environmental sustainability. PVA-CNT membranes offer a promising approach for developing next-generation membranes with optimized structural and functional properties for environmental applications.